2017
DOI: 10.1002/2017gc006943
|View full text |Cite
|
Sign up to set email alerts
|

Rock magnetic and geochemical evidence for authigenic magnetite formation via iron reduction in coal‐bearing sediments offshore Shimokita Peninsula, Japan (IODP Site C0020)

Abstract: Sediments recovered at Integrated Ocean Drilling Program (IODP) Site C0020, in a fore‐arc basin offshore Shimokita Peninsula, Japan, include numerous coal beds (0.3–7 m thick) that are associated with a transition from a terrestrial to marine depositional environment. Within the primary coal‐bearing unit (∼2 km depth below seafloor) there are sharp increases in magnetic susceptibility in close proximity to the coal beds, superimposed on a background of consistently low magnetic susceptibility throughout the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 161 publications
(230 reference statements)
0
6
0
Order By: Relevance
“…Past studies have demonstrated the potential of χ lf as a proxy for identifying the SMTZ in continental margin sediments offshore of Argentina and Uruguay (Riedinger et al, ), southwestern Taiwan (Horng & Chen, ), rapidly deposited sediments offshore of North Island, New Zealand (Rowan & Roberts, ), coal‐bearing sediments, offshore of Shimokita Peninsula, Japan (Phillips et al, ), the Argentine continental slope (Garming et al, ), Nankai Margin, southwestern Japan (Kars & Kodama, , ; Shi et al, ), Cascadia margin offshore of western North America (Housen & Musgrave, ; Larrasoaña et al, ), and Vestnesa Ridge, offshore of western Svalbard (Schneider et al, ; Sztybor & Rasmussen, ). The effects of higher sedimentation rates and sedimentary events (e.g., mass transport deposits) on the sediment geochemical record, especially for reconstructing past methane seepage events, are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have demonstrated the potential of χ lf as a proxy for identifying the SMTZ in continental margin sediments offshore of Argentina and Uruguay (Riedinger et al, ), southwestern Taiwan (Horng & Chen, ), rapidly deposited sediments offshore of North Island, New Zealand (Rowan & Roberts, ), coal‐bearing sediments, offshore of Shimokita Peninsula, Japan (Phillips et al, ), the Argentine continental slope (Garming et al, ), Nankai Margin, southwestern Japan (Kars & Kodama, , ; Shi et al, ), Cascadia margin offshore of western North America (Housen & Musgrave, ; Larrasoaña et al, ), and Vestnesa Ridge, offshore of western Svalbard (Schneider et al, ; Sztybor & Rasmussen, ). The effects of higher sedimentation rates and sedimentary events (e.g., mass transport deposits) on the sediment geochemical record, especially for reconstructing past methane seepage events, are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, only methanogenesis is developed from a modelling perspective (Price & Sowers, ), and though many cell‐damaging reactions would be expected to be common, the growth rate and energetic‐aspects of other metabolisms may not be shared (Lever, ; Lever et al, ). Notable diagenetic processes for which there is a strong microbial component identified at Site C0020 include iron reduction, sulphur reduction as well as carbonate formation (Phillips et al, , ). Similar distinctions could also be made for different types of organic matter (Middelberg, ), for example necromass (organic matter from recently dead organisms), could be tracked separately from sedimentary organic matter with different levels of recalcitrance (Lomstein, Langerhuus, D'Hondt, Jørgensen, & Spivack, ).…”
Section: Discussionmentioning
confidence: 99%
“…We measured bulk, untreated samples containing all lithogenic, biogenic, and authigenic components. These 28 unconsolidated sand samples were selected out of a set of 144 samples originally collected for a separate rock magnetic and geochemical study (Phillips et al, 2017) that covers the full range of major lithologies. The samples measured here are representative of the unconsolidated sands recovered from Hole C0020A.…”
Section: Methodsmentioning
confidence: 99%
“…Flaser bedding, cross bedding, and authigenic carbonate nodules are present in Unit III. Sharp increases in magnetic susceptibility driven by authigenic magnetite precipitation are present in Unit III (Phillips et al, 2017). Unit III represents a nearshore environment with coals derived from brackish wetlands at the top of Unit III and freshwater wetlands at the base of Unit III (Gross et al, 2015).…”
Section: Introductionmentioning
confidence: 99%